2014
DOI: 10.1186/2049-3002-2-18
|View full text |Cite|
|
Sign up to set email alerts
|

Metabolic reprogramming induced by ketone bodies diminishes pancreatic cancer cachexia

Abstract: BackgroundAberrant energy metabolism is a hallmark of cancer. To fulfill the increased energy requirements, tumor cells secrete cytokines/factors inducing muscle and fat degradation in cancer patients, a condition known as cancer cachexia. It accounts for nearly 20% of all cancer-related deaths. However, the mechanistic basis of cancer cachexia and therapies targeting cancer cachexia thus far remain elusive. A ketogenic diet, a high-fat and low-carbohydrate diet that elevates circulating levels of ketone bodie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
209
3
4

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 209 publications
(237 citation statements)
references
References 53 publications
12
209
3
4
Order By: Relevance
“…CR, which prevents or reverse obesity, improves insulin sensitivity, and inhibits the development and progression of a variety of cancer including PDAC [280,281]. CR regimen in PDAC decreases circulating levels of leptin and IGF-1, reduces expression of Glut1, suppresses activation of Akt/mTOR, ERK, STAT3, NF-κB and activates AMPK and SIRT1 [281][282][283] KD, is described as a high-fat and low carbohydrate diet that elevates circulating levels of ketone bodies, serving as an alternative energy source [284] Shukla et al [284] identified that ketone bodies revert metabolic adaptations in PDAC cells to induce growth arrest and apoptosis. Treatment with ketone bodies lead to a a reduction in glucose uptake, glycolytic flux, glutamine uptake, lactate secretion and ATP content in PDAC cells.…”
Section: Diet and Dietary Interventionsmentioning
confidence: 99%
See 3 more Smart Citations
“…CR, which prevents or reverse obesity, improves insulin sensitivity, and inhibits the development and progression of a variety of cancer including PDAC [280,281]. CR regimen in PDAC decreases circulating levels of leptin and IGF-1, reduces expression of Glut1, suppresses activation of Akt/mTOR, ERK, STAT3, NF-κB and activates AMPK and SIRT1 [281][282][283] KD, is described as a high-fat and low carbohydrate diet that elevates circulating levels of ketone bodies, serving as an alternative energy source [284] Shukla et al [284] identified that ketone bodies revert metabolic adaptations in PDAC cells to induce growth arrest and apoptosis. Treatment with ketone bodies lead to a a reduction in glucose uptake, glycolytic flux, glutamine uptake, lactate secretion and ATP content in PDAC cells.…”
Section: Diet and Dietary Interventionsmentioning
confidence: 99%
“…Treatment with ketone bodies lead to a a reduction in glucose uptake, glycolytic flux, glutamine uptake, lactate secretion and ATP content in PDAC cells. 284 Importantly, metabolic reprogramming of tumour cells by ketone bodies is responsible for diminishing cancer cell-induced cachexia in both cell line models and animal models of PDAC. 284 In addition, keeping in view the significant role of inflammation and metabolic alteration, a ketogenic diet also provides an efficient therapeutic strategy, because lowering lactate production by ketogenic diet has been shown to decrease MDSC frequency leading to improved antitumour immune response.285 Remarkably, a ketogenic diet causes minimal side effects as previously demonstrated that a 2-7 mM ketone body concentration can be achieved without giving rise to clinical acidosis.…”
Section: Diet and Dietary Interventionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies using FDG-PET imaging [25,80] or microdialysis measurements [81] have shown that a KD can downregulate the glycolytic tumor metabolism in some patients. A decrease in tumor lactate production has also been observed in mice kept on a KD [82,83] and in cultured cancer cells treated with ketone bodies [84,85] or fasting-mimicking conditions [86,87]. The decreased tumor lactate concentrations after a few days on a KD in head-and-neck cancer patients measured by Schroeder et al [81] are of particular interest, as tumor lactate concentrations have been directly linked to radioresistance in a variety of xenografted head-and-neck tumors that were irradiated using a clinically relevant schedule of 30 fractions over 6 weeks [88,89].…”
Section: Combining Ketogenic Metabolic Therapy With Radiotherapy To Ementioning
confidence: 99%